Tigecycline Reduces Ethanol Intake in Dependent and Nondependent Male and Female C57BL/6J Mice. (14th November 2016) - Bergeson, Susan E.; Nipper, Michelle A.; Jensen, Jeremiah; Helms, Melinda L.; Finn, Deborah A.
Abstract : Background: The chronic intermittent ethanol (CIE) paradigm is valuable for screening compounds for efficacy to reduce drinking traits related to alcohol use disorder (AUD), as it measures alcohol consumption and preference under physical dependence conditions. Air control‐treated animals allow simultaneous testing of similarly treated, nondependent animals. As a consequence, we used CIE to test the hypothesis that tigecycline, a semisynthetic tetracycline similar to minocycline and doxycycline, would reduce alcohol consumption regardless of dependence status. Methods: Adult C57BL/6J female and male mice were tested for tigecycline efficacy to reduce ethanol (EtOH) consumption using a standard CIE paradigm. The ability of tigecycline to decrease 2‐bottle choice of 15% EtOH (15E) versus water intake in dependent (CIE vapor) and nondependent (air‐treated) male and female mice was tested after 4 cycles of CIE vapor or air exposure using a within‐subjects design and a dose–response. Drug doses of 0, 40, 60, 80, and 100 mg/kg in saline were administered intraperitoneally (0.01 ml/g body weight) and in random order, with a 1‐hour pretreatment time. Baseline 15E intake was re‐established prior to administration of subsequent injections, with a maximum of 2 drug injections tested per week. Results: Tigecycline was found to effectively reduce high alcohol consumption in both dependent and nondependent female and male mice. Conclusions: Our data suggest that tigecycline may be a promising drug with novel pharmacotherapeutic characteristics for the treatment of mild‐to‐severe AUD in both sexes. Abstract : The tetracycline class drug, tigecycline, reduced ethanol consumption in the chronic intermittent ethanol model for both dependent and non‐dependent, female and male, C57BL/6J mice.